Analysis of Factors Affecting the Payment of Zakat in Special Capital Region (DKI) of Jakarta - Sedjati, Dwi Poetra; Basri, Yuzwar Z.; Hasanah, Uswatun (International Journal of Islamic Business & Management, 2018)
The objective of this research is for analyzing and describing matters that affect the willingness of the community in the DKI Jakarta in paying the zakat. This is done through a theoretical model of knowledge, attitude, religiousness, motivation, and income of the Muslim community in their payment of the zakat. This model will specifically empirically test the direct effects of knowledge, attitude, motivation, religiousness, and income of the Islamic community to the impacts of the willingness of the Islamic community in paying the zakat. This research is conducted by taking a total of 430 Islam community members as research objects in  5  region  of DKI Jakarta,  by using the purposeful sampling technique. The total of respondents as the research population is 430 persons. For interpreting and analyzing the data, the analytical technique used is the Structural Equation Model (SEM) using the AMOS software. The result of the hypothesis testing has verified that the factors of knowledge, attitude, religiousness, motivation, and income of the Muslim community have significantly increased their willingness to pay the zakat. Also the model used in this research is acceptable and is valid, as indiccated by the appropriateness index, all of which have met the requirements. The results of this study indicate that there is the potential for increasing the zakat revenue through increasing the willingnes/interest of the muzakki to pay the zakat, as such increased interest is affected by the increasing knowledge, attitude, religiousness, motivation, and income of the muzakki.  This has increased the conviction that the zakat has a very strategic function in the economy of the state, namely as one of the instruments for distributing wealth and increase the wellbeing of society as a whole.